2021
DOI: 10.1007/s00068-021-01607-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles as mediators and markers of acute organ injury: current concepts

Abstract: Due to the continued high incidence and mortality rate worldwide, there is a need to develop new strategies for the quick, precise, and valuable recognition of presenting injury pattern in traumatized and poly-traumatized patients. Extracellular vesicles (EVs) have been shown to facilitate intercellular communication processes between cells in close proximity as well as distant cells in healthy and disease organisms. miRNAs and proteins transferred by EVs play biological roles in maintaining normal organ struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 191 publications
(233 reference statements)
1
31
0
Order By: Relevance
“…Despite the many recent advances, considerable gaps remain in our knowledge of the biological mechanisms and functional conditions involved in the release of LEVs, and how they affect the parasite host interaction . The recent research does point to a nano-drug delivery system as a potentially important step forward for the improvement of anti-leishmanial therapy [16]. Similar pathway-oriented analyses should also be used to identify the targets of LEVs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the many recent advances, considerable gaps remain in our knowledge of the biological mechanisms and functional conditions involved in the release of LEVs, and how they affect the parasite host interaction . The recent research does point to a nano-drug delivery system as a potentially important step forward for the improvement of anti-leishmanial therapy [16]. Similar pathway-oriented analyses should also be used to identify the targets of LEVs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Promising new technology, including nanotechnological approaches, have developed over the past few decades to improve the prevention of leishmaniasis, the detection of the parasite, and its treatment [8,[11][12][13]. The importance of the extracellular vesicles has stimulated considerable interest in the scientific community, given their apparent potential for the development of effective diagnostic and therapeutic approaches, including the prediction of the outcome of the interaction between cells [14][15][16][17]. Despite some advances, the mechanisms of the selective packaging of these extracellular vesicles are still poorly understood, and there is no consensus on the differential isolation and characterization of the extracellular vesicles or the ultrasensitive detection of specific extracellular vesicle subtypes, their specific biomarkers or their biogenesis (Figure 2) [5,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes, as a new type of cell-to-cell communication, have shown that they can communicate with cells in healthy and diseased organisms. 30 Cells can secrete exosomes under normal and pathological conditions, but under pathological conditions, the components of RNA and proteins carried by exosomes change, which regulate the biological activity of recipient cells. 31,32 Therefore, exosomes play a bridging role in mediating or inhibiting receptor cells, and they are expected to be used as targeted therapy vectors for disease treatment.…”
Section: Overexpression Of Lnc-aftr Inhibits Apoptosis and Inflammati...mentioning
confidence: 99%
“…In the last decade, EVs have attracted enormous research interest for their promising medical applications [ 77 , 107 , 108 ]. Vesicles may serve as disease diagnostic tools because they transport origin-specific subsets of nucleic acid (e.g., specifics miRNAs) and proteins that likely correlate to cell-type-associated functions [ 109 , 110 ]. These data and other studies quoted in this present review suggest that EVs secreted by infected human macrophages may carry miRNAs and/or protein signatures that closely reflect the associated clinical pathophysiology status in infectious diseases.…”
Section: Macrophage-evs As Diagnostic Markers For Infectious Diseasesmentioning
confidence: 99%